2020
DOI: 10.2147/ijn.s255902
|View full text |Cite
|
Sign up to set email alerts
|

<p>In vivo Glioblastoma Therapy Using Targeted Liposomal Cisplatin</p>

Abstract: Background: Drug delivery systems have demonstrated promising results to cross bloodbrain barrier (BBB) and deliver the loaded therapeutics to the brain tumor. This study aims to utilize the transferrin receptor (TR)-targeted liposomal cisplatin (Cispt) for transporting Cispt across the BBB and deliver Cispt to the brain tumor. Methods: Targeted pegylated liposomal cisplatin (TPL-Cispt) was synthesized using reverse phase evaporation method and thiolated OX26 monoclonal antibody. The formulation was characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Previous studies prepared a variety of Tf-modified nano-preparations, including liposomes, and reported that the transport efficiency of modified drug-containing liposomes across the BBB was significantly higher compared with that of free drugs, indicating that Tf-liposomes can effectively transport drugs across the brain [ 36 , 37 ]. In the current study, four types of liposomes including Tf-ELE/CTX@BLIP, Tf-ELE/CTX@LIP, ELE/CTX@BLIP and ELE/CTX@LIP were prepared.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies prepared a variety of Tf-modified nano-preparations, including liposomes, and reported that the transport efficiency of modified drug-containing liposomes across the BBB was significantly higher compared with that of free drugs, indicating that Tf-liposomes can effectively transport drugs across the brain [ 36 , 37 ]. In the current study, four types of liposomes including Tf-ELE/CTX@BLIP, Tf-ELE/CTX@LIP, ELE/CTX@BLIP and ELE/CTX@LIP were prepared.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin is a chemotherapeutic drug used for treating numerous human cancers, such as prostate cancer, ovarian cancer and bladder cancer [ 68 70 ]. In recent years, studies have found that Cisplatin has been shown to be effective in combination with other drugs in treating patients with GBM [ 71 73 ]. It was inferred that cisplatin might downregulate the expression of HOTAIR.…”
Section: Discussionmentioning
confidence: 99%
“…In recent research, methods to minimize the contribution of the BBB to drug delivery have been explored. These methods include the use of a clinical focused ultrasound device (FUS) and improvement of the delivery system using transferrin-receptor-targeted liposomes [ 46 , 47 , 48 ]. For about 30 years, there have been no alternative drugs for GBM treatment other than TMZ.…”
Section: Clinical Treatment For Overcoming Brain Tumorsmentioning
confidence: 99%